2009
DOI: 10.1055/s-0030-1247773
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus Status at Anterior Cruciate Ligament Reconstruction Associated with Radiographic Signs of Osteoarthritis at 5- to 10-Year Follow-Up –A Systematic Review

Abstract: The development of premature osteoarthritis after anterior cruciate ligament (ACL) reconstruction is a significant cause of morbidity in young, active individuals. Meniscal injuries are frequently noted at the time of reconstruction, and the critical role of an intact meniscus in the prevention of osteoarthritis has been well documented. The purpose of this review is to evaluate the effects of meniscal status at ACL reconstruction on the subsequent development of osteoarthritis. A systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 49 publications
5
106
0
Order By: Relevance
“…Short-and long-term results are good when compared to a subtotal meniscectomy [1][2][3]. Therefore, meniscal repair has become the treatment of choice for traumatic meniscal lesions located in the vascularised area [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Short-and long-term results are good when compared to a subtotal meniscectomy [1][2][3]. Therefore, meniscal repair has become the treatment of choice for traumatic meniscal lesions located in the vascularised area [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The meniscus is vital to normal function and longevity of the knee, as meniscal loss causes increased contact pressures and articular cartilage degeneration [3][4][5][6][7][8] . Meniscal repair techniques have evolved substantially in the last few decades, with open techniques replaced by arthroscopic techniques.…”
mentioning
confidence: 99%
“…However, in a systematic literature review, stable medial meniscal tears left in situ during ACL reconstructions result in the high prevalence of failures, such as residual pain and subsequent meniscus repair (or partial meniscectomy) [21]. In our study, FasT-Fix all-inside meniscus repairs showed complete healing of simple longitudinal medial meniscus tears on second-look arthroscopic evaluation in 100 % of cases.…”
Section: Discussionmentioning
confidence: 50%